A place where sunflowers grow = Sabaku ni saita himawari - Lee-Tai, Amy, 1964- (Children's Book Press, 2006)
While she and her family are interned at Topaz Relocation Center during World War II, Mari gradually adjusts as she enrolls in an art class, makes a friend, plants sunflowers and waits for them to grow.